2015
DOI: 10.1186/s40001-015-0166-9
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme insertion/deletion polymorphism, 24-h blood pressure profile and left ventricular hypertrophy in hypertensive individuals: a cross-sectional study

Abstract: BackgroundThe absence of nocturnal blood pressure dipping (ND) identified by 24-h ambulatory blood pressure monitoring (ABPM) correlates with a worse cardiovascular prognosis. The renin–angiotensin system influences blood pressure levels and the occurrence of target organ damage (TOD). Thus, the aim of this study was to correlate the angiotensin-converting enzyme gene (ACE) insertion/deletion (I/D) polymorphism with the 24-h blood pressure profile and TOD in hypertensive individuals.Methods155 non-diabetic hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 57 publications
(72 reference statements)
0
12
0
4
Order By: Relevance
“…(по кодоминантному типу наследования) в когорте некоренного этноса и в 5 раз -у носителей гетерозиготного генотипа I / D в когорте мужчин-шорцев. Целый ряд исследований свидетельствует о большей предрасположенности к развитию ГЛЖ у больных АГ при наличии у них генотипа D / D гена АСЕ[8,[21][22][23]]. Достоверное увеличение частоты обнаружения генотипа D / D у пациентов с ГЛЖ наблюдали Т. Ishigami и соавт.…”
unclassified
“…(по кодоминантному типу наследования) в когорте некоренного этноса и в 5 раз -у носителей гетерозиготного генотипа I / D в когорте мужчин-шорцев. Целый ряд исследований свидетельствует о большей предрасположенности к развитию ГЛЖ у больных АГ при наличии у них генотипа D / D гена АСЕ[8,[21][22][23]]. Достоверное увеличение частоты обнаружения генотипа D / D у пациентов с ГЛЖ наблюдали Т. Ishigami и соавт.…”
unclassified
“…While there have been arguments about these results, several authors support this conclusion. A study by Cosenso‐Martin and colleagues demonstrated that the presence of the D allele appears to be associated with higher mean 24‐hour and daytime SBP in patients with hypertension. Bautista and associates reported that SBP and DBP were 4.58 and 3.32 mm Hg higher in DD homozygous individuals than in carriers of the I allele, and the DD genotype appears to be an independent risk factor for development of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of II+ID alleles of the I/D polymorphism with a daily intake of more than 2,300 mg of salt was found to be associated with HT and subsequent obesity [47]. The D allele of I/D polymorphism was found to be associated with diastolic and systolic HT, daily variability of HT, and injury to target organs [48][49][50][51][52]. The D/D genotype was shown to play a significant role in the development of CMA-associated cerebral lesions [53,54] and in the prediction of the risk of this lesion [55].…”
Section: The Agt Gene Of Angiotensinogen (Chromosome 1q42)mentioning
confidence: 99%
“…Inhibition of the NOS1 gene in the medulla oblongata and hypothalamus is associated with the pathogenesis of systemic hypertension [57]. A genome-wide association study for Lacunes [35,41], WMH [41] Loss of white matter tract microstructure [46] Not verified [42,45] Found [37,8] Not verified [39,40] AGT rs4762 Not verified [42] Found [37,38] Not verified [39,40] AGT -20A>C WMH [45] Found [45] ACE I/D Alu-sequences WMH [52][53][54][55] Not verified [46] Found [47][48][49][50][51][52] CYP11B2 rs1799998 WMH, expansion of perivascular spaces [36,56] [55,67,68] Found [65,66] PLAT rs2020918 LI [71,72] No data FGB rs1800790 LI [73] No data IL1B rs16944 LI [78], WMH [81] No data IL6 rs1800795 LI [79], WMH [80] Not verified [ [87] No data REVIEWS ischemic stroke risk factors iditified NOS1 as a potential candidate gene…”
Section: Genes Affecting Endothelial Functionmentioning
confidence: 99%